Dispersion of Cheating Behaviours in Online Social Networks - Samreen, Shagufta; Shilpa, K.S; Sneha, K.B; Sneha, Pal; Sagar, B (International Journal of Computer Sciences and Engineering, 2025)
Social contact are know to be spread through human behaviours. The diffusion process on social networks has also been grip to spread the undesirable dispersion.The main attention is to attract the contagion of malicious or even criminal behaviors in online social networks. Here, we study the social contagion problem of cheating behavior found in the massively multiplayer online role playing game (MMORPG) that provides a lifelike environment with rich and realistic user interactions. It has a strong chance of being noticed by their friends and leading them to cheat themselves due to their abnormal behaviour. In this paper, we show the existence of the dispersion of cheating. We then explore various possible social reinforcement mechanisms after introducing several factors to quantify the effect of social reinforcement on the dispersion and analyze the dynamics of bot diffusion in an extensive user interaction log from a major MMORPG.